Early Rehabilitation in Acute Care Inpatient Wards May Be Crucial to Functional Recovery 3 Months After Ischemic Stroke. Issue 1 (30th October 2020) - Wang, Ching-Yi; Chen, Yueh-Chi; Wang, Chun-Hou
Abstract: Objective: Early rehabilitation in acute care inpatient wards may maximize functional outcome at 3 months after stroke in survivors of stroke. It is unknown whether functional change during acute care hospitalization is significantly associated with functional recovery at 3 months in survivors of acute stroke. The purposes of this study were to examine the association of the Barthel Index (BI) at 3 months with functional change as measured with the Barthel Index (ΔBI) in an acute care inpatient ward and to identify the factors associated with ΔBI and who could benefit from an early rehabilitation program. Methods: In this prospective longitudinal study, 76 patients with ischemic stroke in an acute care inpatient ward received early rehabilitation of up to 2 sessions per day for 5 d/wk during their stay. Therapy density was calculated as the proportion of total therapy sessions completed. At admission and discharge, they were assessed with the BI and the Postural Assessment Scale for Stroke Patients (PASS). Demographic and health-related information was also collected. The Barthel Index (BI) was reassessed at 3 months. Results: ΔBI in the acute care inpatient ward significantly predicted the BI at 3 months, over and above the other significant variables; in addition, therapy density and change in PASS were significantly associated with ΔBI. Patients with moderate initial functional dependence had the largest ΔBI, followed by the group with a more severe condition. Conclusions: ΔBI in acute care inpatient wards may be an important predictor of the BI at 3 months. Therapy density and change in PASS were significantly associated with ΔBI. Impact: Survivors of acute stroke who receive up to 2 rehabilitation sessions per day for 5 d/wk early in their hospitalization have better functional recovery at 3 months after stroke.